Antibiotic resistance in probiotic bacteria - Gueimonde, Miguel; Sánchez, Borja; de los Reyes-Gavilán, Clara G.; Margolles, Abelardo (Frontiers in Microbiology, 2013)
Probiotics are live microorganisms which when administered in adequate amounts confer a health benefit on the host. The main probiotic bacteria are strains belonging to the genera Lactobacillus and Bifidobacterium, although other representatives, such as Bacillus or Escherichia coli strains, have also been used. Lactobacillus and Bifidobacterium are two common inhabitants of the human intestinal microbiota. Also, some species are used in food fermentation processes as starters, or as adjunct cultures in the food industry. With some exceptions, antibiotic resistance in these beneficial microbes does not constitute a safety concern in itself, when mutations or intrinsic resistance mechanisms are responsible for the resistance phenotype. In fact, some probiotic strains with intrinsic antibiotic resistance could be useful for restoring the gut microbiota after antibiotic treatment. However, specific antibiotic resistance determinants carried on mobile genetic elements, such as tetracycline resistance genes, are often detected in the typical probiotic genera, and constitute a reservoir of resistance for potential food or gut pathogens, thus representing a serious safety issue.